Night-shift work and psychiatric treatment. A follow-up study among employees in Denmark - Karen Albertsen; Harald Hannerz; Martin L Nielsen; Anne Helene Garde (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: We aimed to test the hypotheses that night-shift work is associated with an increased incidence of (i) redeemed prescriptions for psychotropic medicine and (ii) psychiatric hospital treatment due to mood, anxiety or stress-related disease. Moreover, we aimed to assess whether (iii) the effect of night-shift work on the rates of antidepressants differs from the effects on the rates of anxiolytics and (iv) the association between night-shift work and psychotropic medicine is affected by long working hours. METHODS: Full-time employees who participated in the Danish Labor Force Survey sometime in the period 2000-2013 (N=131 321) were followed for up to five years in national registers for redeemed prescriptions and psychiatric hospital treatment. The analyses were controlled for sex, age, weekly working hours, calendar time of the interview and socioeconomic status. RESULTS: We detected 15 826 cases of psychotropic drug use in 521 976 person-years at risk and 1480 cases of hospitalization in 636 673 person-years at risk. The rate ratio (RR) for psychotropic drugs was estimated to be 1.09 [99% confidence interval (CI) 1.02-1.16] for night-shift versus no night-shift work. The corresponding RR for psychiatric hospital treatment was 1.11 (95% CI 0.95-1.29). The odds of redeeming a prescription for antidepressants rather than anxiolytics was independent of night-shift work: 1.09 (95% CI 0.96-1.24), and we found no interaction effect between night-shift work and working hours (P=0.26). CONCLUSION: As it appears in the general working population in Denmark, night-shift work is not an important predictor of mental ill health.